Aluminum-induced change in cell-wall polysaccharide content of wheat roots in relation to aluminum tolerance of wheat - LIN Xian-yong; TANG Jian-feng; LI Gang; ZHANG Yong-song (浙江大学学报. 农业与生命科学版, 2005)
The effects of aluminum (Al) on root elongation and the amount of cell-wall polysaccharides in roots were examined in Al-resistant (Xiaimai-1) and Al-sensitive (Fu-84) genotypes of wheat (Triticum aestivum L.). Root elongation of both genotypes was markedly inhibited when wheat roots were exposured to 30 μmol/L AlCl3 solutions for 24 h and the inhibition of root elongation was more conspicuous in the Al-sensitive genotype (Fu-84). The Al content was significantly higher in 0-10 mm root segments than in 10-20 mm root segments and the Al content of 0-10 mm root segments in Fu-84 was 1.3 times that in Xiaimai-1. The amount of pectin uronic acid in 0-10 mm root segments increased under Al stressed condition, especially in the Al-sensitive genotype Fu-84. Whether the roots were exposed to Al or not, the pectin uronic acid content of 0-10 mm root segment cell wall was higher in Fu-84 than in Xiaimai-1, but exposure to Al did not influence the total sugar content of wheat roots. Al did not influence the amount of uronic acid and total sugar in hemicelluloses and cellulose of 10-20 mm root segments, but the amount of hemicellulose 1 (HC1), hemicellulose 2 (HC2) and cellulose in 0-10 mm root segment were increased under Al-stressed condition, which was especially conspicuous in Al-sensitive genotype Fu-84. These findings suggest that Al tends to modify the metabolism of cell-wall polysaccharides and thus make the cell wall more thick and rigid, thereby inhibiting the growth of wheat roots.